A systematic literature review on sustainable production indicators to assess the sustainable performance of industries - Abbass, Nazik Mahmoud; Abd Rahman, Azmawani; Ab. Aziz, Yuhanis; Sidek, Shafie (Human Resource Management Academic Research Society, 2019)
Previous literature proposed various methodologies to integrate and assess sustainable production. Numerous frameworks and indicators for sustainable production were suggested as measurement tools. However, these tools need to be more comprehensive and simpler to apply at factory level to achieve the sustainability goals. This paper mainly aims to analyze the various frameworks of sustainable production as evidenced in previous studies to determine the elements and components of the reviewed frameworks as well as indicators based on their criteria as suggested in the literature. The second objective is to understand the trend of scholars in integrating sustainable performance in manufacturing firms. The scientific literature on sustainable production in manufacturing industries was systematically reviewed. Findings of the study suggest that proposals for sustainable production indictors need to be more detailed to include all sustainable development pillars. Scholars are most likely to propose specific sets of indicators for specific products in industry, and life cycle approach is the most reliable in the case of sustainable production. This review will help to enhance managers’ awareness of different frameworks of sustainable production, which can be used in specific contexts.